Dr Effect of a Healthy-psychological Course in Levels of Serum Uric Acid and the Psychology of Pessimism and Depression in the Elderly: Effect of a Healthy-psychological Course in Levels of Serum Uric Acid and the Psychology of Pessimism and Depression in the Elderly - Luma , A. Jallu; Agharid, S. Abdulridha2 (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The aim of research is to preparation of a healthy - psychological course and the knowledge of its impact on the level of serum uric acid (SUA) and the level of pessimism and depression. The research sample was limited of teaching staff of the Iraqi state universities in Baghdad whom were retired at age of (63-65) years. In order to collect their data, the experimental method used for one group with the pre and post-tests. The study sample consisted of 21 people who have the cases of pessimism and depression. The sample was randomly chosen according to their agreement to do pre and post tests and to be subjected to healthy-psychological approach. After collecting the data obtained from the sample and processing them statistically, the results showed that the healthy -psychological- course has a positive effect on both the levels of Serum Uric Acid, pessimism and depression of the Research sample.